2017
DOI: 10.14701/ahbps.2017.21.4.212
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preoperative biliary stenting on post-operative infectious complications in pancreaticoduodenectomy

Abstract: Backgrounds/AimsThe impact of pre-operative biliary stenting (PBS) in patients undergoing pancreaticoduodenectomy on post-operative infectious complications is unclear. Therefore, the purpose of this study is to investigate the relationship between PBS and post-operative infectious complications, to determine the effect of PBS on bile bacteriology, and to correlate the bacteriology of bile and bacteria cultured from post-operative infectious complications in our institute.MethodsDetails of 51 patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 24 publications
(56 reference statements)
5
18
0
Order By: Relevance
“…We acknowledge limitations of this non-randomized study, including relatively small sample size. Many studies reported that bile is contaminated in patients undergoing PD after biliary drainage [610, 20, 21]. Our study agrees with the importance of surveillance bile culture for management of patients with PD.…”
Section: Discussionsupporting
confidence: 89%
“…We acknowledge limitations of this non-randomized study, including relatively small sample size. Many studies reported that bile is contaminated in patients undergoing PD after biliary drainage [610, 20, 21]. Our study agrees with the importance of surveillance bile culture for management of patients with PD.…”
Section: Discussionsupporting
confidence: 89%
“…Also, Ng et al, reported a high incidence of overall infectious complications in the group of PBD than the other group without drainage (77% versus 67%, respectively). Wound infection was the highest complication (41%) of the infectious ones, followed by IAA (29%) (16), as observed in our study. But we had a lower incidence of infectious complications than the former study.…”
Section: Discussion Discussionsupporting
confidence: 85%
“…Many studies observed polymicrobial organisms in bile cultures withdrawn during the surgery in patients with biliary stenting. E-coli and Klebsiellapneumoniae were the most common bacterial infection (16,26) as reported in our study. Other large volume studies are needed for the justification of the optimal time of PD needed before surgery to have a better outcome.…”
Section: Discussion Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…5,6 Previous studies showed an association between preoperative biliary drainage, contamination of intraoperative bile cultures (IOBCs) and the occurrence of postoperative infectious complications, particularly SSIs. 1,[7][8][9][10] Although biliary drainage is not routinely recommended, the number of patients requiring this preoperative procedure is expected to rise due to the increasing use of neoadjuvant chemotherapy in pancreatic cancer. 11,12 Patients with a biliary stent appear to have different IOBC contamination patterns.…”
Section: Introductionmentioning
confidence: 99%